Analisis Sistem Distribusi Air Bersih di Perumahan Ciomas Permai Kabupaten Bogor Jawa Barat: Analysis of Water Distribution System at Ciomas Permai Residence Bogor Regency West Java - Fauziah, Kiki Rizky; Pandjaitan, Nora; Karunia, Titiek Ujianti (Departemen Teknik Sipil dan Lingkungan IPB, 2021)
Water distribution systems are often problematic in terms of quantity, pressure, continuity and quality. The research aimed to analyze water distribution system of PDAM Tirta Kahuripan Kabupaten Bogor in Ciomas Permai Residence. The research was conducted by collecting primary and secondary data. Analysis of clean water distribution system was carried out using the EPANET 2.0. Ciomas Permai Residence was located in zone 6 of PDAM Tirta Kahuripan servive areas. The result showed that the quality of the distributed water was in accordance with the applicable standard and continuous for 24 hours even though there were significant discharge differences during peak hours. Based on the measurement on Sunday and Monday, the minimum discharge were 14.4 l/sec and 13.8 l/sec respectively, higher than customer requirements of 7.34 l/sec, The water distribution pressure ranged from 0.7 - 1.35 bar. The result of clean water distribution simulation using EPANET 2.0 showed that the velocity of water and headloss were not accordance with the applicable standards.